Diagnosa Penyakit Fibroadenoma Mammae Menggunakan Metode Certainty Factor Dengan Penelusuran Forward Chaining - Antonius, Roni; Simangunsong, Agustina; Sinaga, Anita Sindar RM (Jurnal ICT : Information Communication & Technology, 2019)
Mammae Fibroadenoma Disease (FAM) is a benign neoplasm that has dense and capsule features. Is the most common type of breast disease. Usually attacks women under 25 years. In this study detection of Fibroadenoma Mammae (FAM) was carried out using the Forward Chaining method. Aims to detect early FAM disease. To prove a certain or uncertain event. The CF hypothesis is influenced by evidence. CF part of the Expert System is suitable for diagnosing something that is uncertain. The CF method can only process 2 weights in one calculation. There are no rules for combining weights, because for any combination the results will remain the same. In the expert system application design method Forward Chaining, CF (H, E) the value of certainty given by experts to a rule, while CF (E, e) is the value of trust given by the user to the symptoms experienced.